The development of the tenageer’s reproductive health module - Nurwinda Sulistyawati; Daharnis Daharnis; Yarmis Syukur (International Conferences on Educational, Social Sciences and Technology)
Adolescence need to understand and maintain their reproductive health. However, not all adolescents understand and able to maintain their reproductive health. Therefore it is necessary to reference the maintenance and development of adolescent reproductive health.The purposes of this research are to produce the guidance and counseling moduleabout senior high school teenager’s reproductive health which is valid andusable. The method of this research is the development research which used the ADDIE model(Analyze, Design, Development, Implementation, and Evaluation).The subject of this research consists of 6 experts and 40 school counselors. The results of this research show that the guidance and the counseling moduleabout senior high school teenager’s reproductive health is valid and usable to be used by school counselor to improve the understanding and prevent the problems in teenager’s reproductive.